Mencari Solusi Konstitusional untuk Integrasi Nasional - Ni'matul Huda (Unisia, 2003)
When freedom of speech arises in this reformation era, the voice for creation the more just and democratic governance appears every time. Integralism state, then, believed as not  relevant anymore to accommodate the plurality of society, and conversely, federalism which is becoming more popular today, seems to be more appropriate for Indonesia. However, before going further to federalism, local autonomy is regarded as a promising instrument to set up national integrity.